Initially, the function depends on the variable 'x'; then the variable is 'x+1', so you just have to substitute that variable in the equation, for example:
If f(x)= x^2 - 2x +3, then f(x+1)= (x+1)^2 - 2(x+1) +3 = x^2+2x+1-2x-2+3 = x^2+2
hey everyone!! so i'm brand new to this forum and am taking a pre-calculus class and am just going through a book on my own time before starting the class. I'm familiar with lots of these things but as my title says, i'm a little rusty. so i just had a couple simple questions here regarding a couple functions.
AND PLEASE SPELL OUT THE ANSWERS STEP-BY-STEP WITH MAYBE SOME EXPLANATION, my book just gives me the answer without any steps
#1)
Given f(x)= x^2 - 2x +3
Find f(x+1)
****The answer in the book I'm using is x^2 +2**** and i can't quite seem to see why
#2 (and perhaps related to why I can't quite get the first question)
Given w = z(m) = 3m^2 -10
Find z(x-1)
****The annswer in the book i'm using is 3x^2-6x-7
Thanks!!!!!!
Initially, the function depends on the variable 'x'; then the variable is 'x+1', so you just have to substitute that variable in the equation, for example:
If f(x)= x^2 - 2x +3, then f(x+1)= (x+1)^2 - 2(x+1) +3 = x^2+2x+1-2x-2+3 = x^2+2